KARAKTERISTIK PERMUKAAN PATAH DAN KETAHANAN LELAH PADA MATERIAL BEJANA TEKAN BAJA ASTM A36 - Azhari, Ikbal; Chandra, Hendri; Homzah, Ozkar F.; Ramadhoni, Tri Satya; Sampurno, Rachmat Dwi (Politeknik Negeri Sriwijaya, Indonesia, 2024)
Pressure vessels are equipment in the industrial field to hold pressurized fluids, such as gas, oil and chemicals, ASTM A36 steel is one type of material that can be used in pressure vessels, this steel has good mechanical properties but still has limitations in its fatigue resistance. Pressure vessels receive internal and external loads, this pressure difference results in stress on the wall (shell). This stress can cause material damage, therefore the author conducted fatigue repeated bending and Scanning electron microscopy (SEM) testing to analyze fatigue resistance and fracture surface characteristics. Fatigue testing of 4 specimens with angle variations of 4Ëš, 8Ëš, 11Ëš and 13Ëš resulted in a cycle count of 1490200 cycles, 400050 cycles, 234200 cycles and 99000 cycles respectively. SEM results of the fracture surface of the 4Ëš and 13Ëš testing angles of ASTM A36 steel showed striation and microvoid coalescence and crack propagation indicating that the fatigue failure that occurred was ductile fracture. Based on the conclusions obtained, it shows that the number of cycles is influenced by the testing stress, which means that at high stresses, the life time of the pressure vessel will be smaller and vice versa.